Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài

Những câu hỏi liên quan
Nguyễn Quốc Tứ
Xem chi tiết
Nguyễn Quốc Tứ
Xem chi tiết
Nguyễn Thành Đạt
Xem chi tiết
Nguyễn Lê Phước Thịnh
29 tháng 12 2021 lúc 14:17

Câu 1: C

Pham Trong Bach
Xem chi tiết
Cao Minh Tâm
3 tháng 1 2017 lúc 6:32

Chọn D

Thư Nguyễn Anh
Xem chi tiết
vo phi hung
23 tháng 12 2018 lúc 17:19

a ) Ta có : f(2) = 5 

\(\Leftrightarrow\hept{\begin{cases}f\left(x\right)=f\left(2\right)\\\text{ax}-3=5\end{cases}}\)

\(\Leftrightarrow\hept{\begin{cases}x=2\\a.2-3=5\end{cases}}\)

\(\Leftrightarrow\hept{\begin{cases}x=2\\a=4\end{cases}}\)

Vậy a = 4 

b ) Ta có : f(0) = 3

\(\Leftrightarrow\hept{\begin{cases}f\left(x\right)=f\left(0\right)\\\text{ax}+b=3\end{cases}}\)

\(\Leftrightarrow\hept{\begin{cases}x=0\\a.0+b=3\end{cases}}\)

\(\Leftrightarrow\hept{\begin{cases}x=0\\b=3\end{cases}}\) ( 1 ) 

Ta có : f ( 1 ) = 4 

\(\Leftrightarrow\hept{\begin{cases}f\left(x\right)=f\left(1\right)\\\text{ax}+b=4\end{cases}}\)

\(\Leftrightarrow\hept{\begin{cases}x=1\\a.1+b=4\end{cases}}\)

\(\Leftrightarrow\hept{\begin{cases}x=1\\a+b=4\end{cases}}\) ( 2 ) 

Thay b = 3 ở ( 1 ) vào a+b=4 ở ( 2 ) ta được : a + 3 = 4    

                                                                         a       = 1 

Vậy a = 1 ; b = 3 

Ten12
Xem chi tiết
Nguyễn Ngọc Linh
Xem chi tiết
Tuyền
Xem chi tiết
Nguyễn Lê Phước Thịnh
2 tháng 1 2022 lúc 13:33

Câu 4: A

Câu 6: B

duong thu
2 tháng 1 2022 lúc 13:43

4 là a

6 là b

Nguyễn Hà Giang
Xem chi tiết
Nguyễn Thanh An
Xem chi tiết